Concurrent validity and reliability of iVMES portable force plate for measuring vertical jump height - Alvurdu, S.; Akarcesme, C.; Altundag, E.; Montalvo, S. (Journal of Physical Education and Sport, 2024)
This study examined the validity and intrarater reliability of a newly developed portable force platform designed to estimate vertical jump height. Thirty-two healthy, recreationally active sports science students (20 males and 12 females) participated. A total of 64 countermovement jumps (with arm swing) were simultaneously recorded using 2 instruments: the Optojump photoelectric system (Microgate, Bolzano, Italy) as the criterion instrument, and the portable force plate (iVMES, Ankara, Turkey) as the practical instrument, to evaluate validity and reliability. The concurrent validity of the iVMES portable force plate system was examined using the Pearson`s correlation coefficient with 95% confidence intervals and limits of agreement. The typical error of estimate was reported, and Bland-Altman plots were created to evaluate the agreement between the 2 measurement devices. The test-retest reliability of the iVMES force plate was assessed using the intraclass correlation coefficient with a 95% confidence interval. Additionally, metrics such as the smallest error of measurement, smallest worthwhile change, minimum detectable change, and root mean quare error were calculated to assess the absolute reliability. Compared with the criterion instrument, the iVMES force plate produced vertical jump height values with an excellent intraclass correlation coefficient (0.98) and a very low bias (0.14 cm). Furthermore, the test retest reliability was outstanding, with a low coefficient of variation (3.8%) and a strong intraclass correlation coefficient (0.96) for vertical jump height. The measurements from the 2 devices displayed extremely low smallest error of measurement and smallest worthwhile change values (both 0.05), as well as minimum detectable change (0.14) values. These findings confirmed a minimal and acceptable margin of error between the 2 measurements. In conclusion, the iVMES portable force plate demonstrated strong concurrent validity and excellent test-retest reliability for estimating vertical jump height.